First record of Dahliphora sigmoides Schmitz (Diptera: Phoridae) in Malaysia on animal carcass in concealed environment - Raja Muhammad Zuha Raja Kamal Bashah,; See, Huong-Wen; Disney, L.; Baharudin Omar,; Henry, R. (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2014)
Dahliphora sigmoides Schmitz (Diptera: Phoridae) was recorded for the first time in Malaysia, occurring on animal carcass placed in garbage bin at Forensic Science Simulation Site, Universiti Kebangsaan Malaysia, Bangi. This finding expands the knowledge of its distribution in this region. Notes on the species description, its locality and collection procedure are presented herein.